2012
DOI: 10.1111/cas.12007
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of GATA1 dysfunction to multi‐step leukemogenesis

Abstract: In mammals, hematopoietic homeostasis is maintained by a fine-tuned balance among the self-renewal, proliferation, differentiation and survival of hematopoietic stem cells and their progenies. Each process is also supported by the delicate balance of the expression of multiple genes specific to each process. GATA1 is a transcription factor that comprehensively regulates the genes that are important for the development of erythroid and megakaryocytic cells. Accumulating evidence supports the notion that defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 67 publications
(148 reference statements)
0
17
0
Order By: Relevance
“…40 Beside the NF-κB pathway, in agreement with a recent report, 36 in our methylated genes data set we found an enrichment of binding sites for transcription factors such as GATA1 or SP1 that are altered in hematologic malignancies. 41 These results suggest that the inappropriate methylation of CpGs may prevent proper binding of these transcription factors, indirectly altering their participation in the transcription of necessary genes.…”
Section: Discussionmentioning
confidence: 99%
“…40 Beside the NF-κB pathway, in agreement with a recent report, 36 in our methylated genes data set we found an enrichment of binding sites for transcription factors such as GATA1 or SP1 that are altered in hematologic malignancies. 41 These results suggest that the inappropriate methylation of CpGs may prevent proper binding of these transcription factors, indirectly altering their participation in the transcription of necessary genes.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, GATA1‐null cells in a heterozygous female background would be eliminated by apoptosis. Thus, additional genetic events that may occur in the proliferating GATA1.05 progenitor population can lead to leukemic transformation . Interestingly, older GATA1.05 mice also develop CD19+ B‐cell leukemia through a leukemogenic mechanism that is not yet understood, but may be related to lineage commitment skewing toward lymphoid fates by proliferating progenitors expressing low levels of GATA1 …”
Section: The Effects Of Artificially Altering Gata1 Protein Levelsmentioning
confidence: 99%
“…GATA2 participates in proliferation and differentiation of hematopoietic cell lineages. Although GATA1 is also expressed in erythroid precursors, megakaryocytes, and eosinophils (34), the identity of aa among GATA3 or GATA2 and GATA1 is high in zinc finger domains but low in other regions. It was reported that mutations of one allele of GATA2 participate in hematopoietic or immune system diseases (35,36).…”
mentioning
confidence: 99%